QUANTITATIVE AND QUALITATIVE EFFECTS OF 010K - LACTOBACILLUS PARACASEI AND THE "ECOPROBIOTIC" PROBIOTIC PREPARATION ON THE GROWTH AND INTESTINAL MICROFLORA OF FISH (Experimental biology, 2022)
The most important result of fish rearing in closed water systems is to achieve the highest possible growth rate while creating optimal aqueous environment factors. The growth of fish is influenced by many factors, including probiotics in artificial diets. In this sense, functional food supplements, including pro-, pre- and synbiotics, are gaining increasing attention as an environmentally sound strategy to improve fish health. Probiotics, participating in digestive processes, affect the metabolism of the host organism, promote protein synthesis and increase the degree of their assimilation. The aim of this study was to investigate the effects of the 010K - Lactobacillus paracasei strain that isolated from Kazakhstan koumiss and the "Ecoprobiotic" probiotic preparation on the growth of intestinal microflora in Nile tilapia. The study outcomes displayed that live weight of fish in the experimental groups (010K - Lactobacillus paracasei and probiotic preparation "Ecoprobiotic") was higher than in the control group. Moreover, fish fed with the "Ecoprobiotic " probiotic and 010K - Lactobacillus paracasei strain had a significantly higher number of yeast cells compared to the control group. In summary, the 010K - Lactobacillus paracasei and probiotic preparation "Ecoprobiotic" may be a promising candidate for the improving growth and intestinal microbiota of Nile tilapia.